EVALUASI KINERJA RUAS JALAN DAAN MOGOT – JALAN BOURAQ DENGAN PEMBERLAKUAN SISTEM SATU ARAH - Riski Wahyudi; Avin Barra Ramadhan; Raka Surya Pradana (Journal Information Technology Engineering and Science (JITES), 2025)
Tangerang City plays a strategic role as an administrative and economic hub in Banten Province. This position has contributed to increasing traffic volumes, particularly along Daan Mogot Road, which functions as a primary urban corridor with high mobility intensity. This study aims to evaluate and compare traffic performance and road service levels under two scenarios: the existing two-way traffic system and the implementation of a one-way system on Daan Mogot Road and its alternative route, Bouraq Road. Traffic data collected include traffic volume, roadway geometry, and vehicle speed, which were used to calculate the degree of saturation (DJ), free-flow speed, travel speed, and level of service. The traffic performance analysis was conducted based on the Indonesian Highway Capacity Manual (PKJI, 2023), while service level classification refers to the Ministry of Transportation Regulation No. PM 96 of 2015. The results indicate that the implementation of the one-way system significantly improved traffic performance. On Daan Mogot Road, the DS decreased from 0.75 (eastbound) and 0.60 (westbound) to 0.43 (westbound). Similarly, on Bouraq Road, the (DJ) reduced from 0.60 (westbound) and 0.56 (eastbound) to 0.25 (eastbound). Vehicle speeds also showed a marked increase, rising from 35–55 km/h under the two-way configuration to 51–65 km/h after the one-way system was applied. In conclusion, the implementation of one-way traffic management on the study corridor proved effective in enhancing traffic performance, decrease (Dj) as evidenced by 47.92%.